To the Point: Integrating the Obstetrics and Gynecology Core Clerkship into a Longitudinal Integrated Curriculum in US Medical Schools - Pradhan, Archana (Med Sci Educ, 2020)
This article, from the “To the Point” series that is prepared by the Association of Professors of Gynecology and Obstetrics (APGO) Undergraduate Medical Education Committee, is a review of issues to consider when integrating obstetrics and gynecology into a Longitudinal Integrated Clerkship (LIC) model. The background, objectives, and outcomes related to LIC are discussed. Specific challenges and solutions for structuring an LIC in the context of obstetrics and gynecology are examined, which include student/faculty issues as well as process matters such as general infrastructure and specific curriculum concerns.